Effect of Early Supplemental Formula Intervention on Body Weight and Hyperbilirubinemia in Neonates During 72 h After Birth - Zhao, Lu-Lu; Lee, En-Pei; Kuo, Raymond Nein-Chen; Yang, Stephen Shei-Dei; Huang, Su-Cheng; Wu, Han-Ping (Frontiers in Pediatrics, 2021)
Background: The full breastfeeding may lead to insufficient milk intake of newborns and increase the rate of body weight loss (BWL). Severe BWL was generally believed as a cause of significant hyperbilirubinemia in newborn babies. The study aimed to investigate the effect if early supplemental feeding in newborns with birth weight loss at the first 3 days after birth could decrease the rate of hyperbilirubinemia 72 hours of birth. Methods: A total of 395 neonates with gestational age >37 weeks and birth body weight >2500g were prospectively collected between 2016 and 2018. We analyzed 280 neonates with BWL rate reaching the predictive value (4.5%, 7.5%, and 8% on the first, second, third day after birth, respectively) for subsequent hyperbilirubinemia after 72 hours after birth. The enrolled cases were divided into four subgroups as interventional consecutive milk supplement for 0, 1, 2, and 3 days after birth for further analysis Results: For newborns with BWL reaching the predictive value on the first day after birth, the serum bilirubin levels were lower in the experimental group than those in the non-involved control group (p<0.05). For newborns with three consecutive days of interventional milk supplementation, the serum bilirubin levels at the 72 hours after birth showed the lowest levels compared with the other sub-groups with two consecutive days and one consecutive day of interventional milk supplementation (p<0.05). Moreover, there was a significantly decreasing trend in the consecutive days of interventional milk supplementation (p<0.05). Conclusion: Newborns with BWL over 4.5% on the first day after birth receiving early intervention milk supplementation could significantly reduce serum bilirubin levels at the 72 hours after birth. The more days of consecutive milk supplementation after birth may lead to the lower the 72 hours serum bilirubin levels. It is recommended to early and consecutive milk supplementation after birth to be an effective way in reducing serum bilirubin levels.